Avaliação térmica em telhas com material reciclado para serem utilizadas em construções rurais - (:unkn) unknown (Universidade Federal do Pampa, 2017)
At present, the need for recovery of the environment and natural resources is remarkable and growing, making recycling and reuse of materials one of the most suitable and used solutions, giving rise to products considered ecological, which are applied in several areas, including construction and its respective divisions, such as engineering for rural purposes. In this context, it becomes important the knowledge of several products used in this area, such as tile made from recycled material from long-life packaging or Tetra Pak. The Tetra Pak packaging has many characteristics, being aseptic and composed of layers with different materials, which act as a barrier, preventing the entry of light, air, water and microorganisms and also prevents the aroma of the food from coming out of the packaging. It is extremely important the knowledge of several characteristics of tiles made from recycled packages, the objective of this work being to evaluate the thermal comfort of the tile considered ecological in comparison with the metallic tile and fiber cement. The experiment was carried out in the Experimental Area of the Federal University of Pampa, where small scale structures were constructed for the three different types of roof tiles. It was verified that the tile made of recycled material can be used in rural constructions with thermal comfort in its use, in compliance with the technical norms, because it presents lower temperature values in its interior, compared to the traditional tiles models.
Keywords: Engenharia agrícola; Construções rurais; Telha ecológica; Reciclagem; Agricultural engineering; Ecological tile; Recycling; Construction; CNPQ::CIENCIAS AGRARIAS